High-temperature-resistant ceramic-based resin composite material as well as preparation method and application thereof
By modifying the combination of phenolic resin and ceramic reinforced slurry and fiber material, an efficient high-temperature resistant ceramic-based resin composite material is formed, which solves the problem of insufficient use time of existing materials in ultra-high temperature environments, and realizes the dense structure of the material and Excellent mechanical properties, suitable for ultra-high temperature applications.
Patent Information
- Application Number
- CN202411437694.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing silicon carbide fiber composite materials cannot meet the requirements of long-term use in ultra-high temperature environments above 2000°C, which limits its application in the field of ultra-high temperature.
Modified phenolic resin and ceramic reinforced slurry are combined with carbon fiber cloth or quartz cloth, and a dense ceramic structure is formed by multiple coatings and hot pressing treatments, improving the high temperature and mechanical properties of the material.
Under the ultra-high temperature environment of 2000℃, the material structure remains intact, has small expansion, excellent mechanical properties, and can be used for a long time, meeting the application requirements of composite materials at high temperatures.
Smart Images

Figure CN119217806A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of silicon carbide ceramic preparation, and in particular relates to a high temperature resistant ceramic-based resin composite material and a preparation method and application thereof. Background Art
[0002] Silicon carbide fiber composite materials are considered to be ideal materials to replace high-temperature alloy materials due to their high strength, low density, high temperature resistance and other characteristics. They can withstand higher temperature thermal oxidation environments and maintain the material state stability under high temperature environments. However, the existing use of inorganic fillers and ablation-resistant resins as a matrix resin, reinforced with carbon fiber or quartz fiber, chemical reactions occur during the curing process to prepare high-temperature resistant composite materials, which can only be used at high temperatures. Therefore, it is necessary to modify its performance to improve its application in ultra-high temperature fields.
[0003] The prior art with application publication number CN 110194609 A discloses a high-temperature resistant, oxidation-resistant ceramic resin composite material, which is a resin composite material made of a carbon-based resin as a matrix and a ceramic powder mixed with a supporting filler, a fusible filler and a reactive filler as a filler. The resin composite material can be used for a long time (>1000s) in an oxidizing atmosphere at 1400°C-1700°C without obvious ablation.
[0004] However, existing silicon carbide fiber composite materials are mainly designed for long-term use in the atmosphere or oxygen-rich environment at 1400℃-1700℃, and cannot meet the requirements of long-term use in ultra-high temperature thermal environments above 2000℃, which hinders their development and application in the ultra-high temperature field. Summary of the invention
[0005] The present application discloses a high temperature resistant ceramic-based resin composite material and a preparation method and application thereof, aiming to solve the technical problem that existing resin composite materials cannot meet the requirements of long-term use in ultra-high temperature thermal environments.
[0006] In order to achieve the above purpose, the technical solution of this application is:
[0007] A first aspect of the present application provides a high temperature resistant ceramic-based resin composite material, the composite material comprising a fiber material matrix and a modified phenolic resin and a ceramic reinforcing slurry composited on the fiber material matrix.
[0008] The fiber material matrix includes one of carbon fiber cloth, quartz cloth or silicon carbide fiber cloth;
[0009] The modified phenolic resin is POSS modified phenolic resin;
[0010] The raw materials for preparing the ceramic reinforcement slurry include, by mass: 5-10 parts of silicon carbide powder, 15-45 parts of tantalum nitride powder, 1-10 parts of nickel powder, 10-25 parts of asphalt, and 35-50 parts of modified phenolic resin.
[0011] In combination with the first aspect, preferably, the raw materials for preparing the ceramic reinforcement slurry include, by mass: 6-8 parts of silicon carbide powder, 25-35 parts of tantalum nitride powder, 4-8 parts of nickel powder, 15-20 parts of asphalt, and 40-45 parts of modified phenolic resin.
[0012] In combination with the first aspect, preferably, the diameter of the silicon carbide powder is 200-400 nm;
[0013] And / or, the diameter of the tantalum nitride powder is 200-400 nm;
[0014] And / or, the nickel powder has a diameter of 10-40 μm.
[0015] In combination with the first aspect, preferably, the modified phenolic resin is added in an amount of 0.3-0.7 times that of the resin composite material.
[0016] The second aspect of the present application provides a method for preparing the high temperature resistant ceramic-based resin composite material according to the first aspect, the method comprising:
[0017] The fiber material matrix is immersed in a modified phenolic resin solution and then dried to obtain a primary modified material;
[0018] Applying the ceramic reinforcing slurry on the surface of the primary modified material to obtain a secondary modified material;
[0019] calcining the secondary modified material to obtain a tertiary modified material;
[0020] Applying the ceramic reinforcing slurry on the surface of the tertiary modified material to obtain a quaternary modified material;
[0021] The four modified materials are laminated and then subjected to hot pressing to obtain the high temperature resistant ceramic-based resin composite material.
[0022] In combination with the second aspect, preferably, the concentration of the modified phenolic resin solution is 5-20%;
[0023] and / or, the fiber material matrix is immersed in the solution of modified phenolic resin for 24-48 hours;
[0024] And / or, the drying temperature is 60-80°C.
[0025] In combination with the second aspect, preferably, the concentration of the ceramic reinforcement slurry is 10-20%.
[0026] In combination with the second aspect, preferably, the secondary modified material is calcined at a temperature of 400-600° C. for a time of 0.5-2 h.
[0027] In combination with the second aspect, preferably, the temperature of hot pressing after laminating the four modified materials is 150-200° C. and the time is 1.5-3 h.
[0028] The third aspect of the present application provides the use of the high-temperature resistant ceramic-based resin composite material produced by the preparation method described in the second aspect in the preparation of turbine rotors.
[0029] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:
[0030] The high-temperature resistant ceramic-based resin composite material provided by the present application is obtained by compounding POSS-modified phenolic resin and ceramic reinforcing slurry on a fiber material matrix. On the one hand, it can give the resin composite material excellent high-temperature resistance. After ultra-high temperature treatment at 2000°C (10 minutes), the material microstructure is dense and the overall structure is complete, which can meet the requirements of continuous use in ultra-high temperature environments; on the other hand, it can give the resin composite material excellent mechanical properties, and has less expansion in a continuous ultra-high temperature environment, and can maintain excellent mechanical properties after ultra-high temperature treatment; finally, it can be maintained for a long time in an ultra-high temperature environment with a high quality retention rate, meeting the application requirements of the composite material at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 The scanning electron microscope images of the first modified material and the third modified material in the A1-high temperature resistant ceramic-based resin composite material prepared in the embodiment of the present application;
[0033] Figure 2 The scanning electron microscope images of the A1-high temperature resistant ceramic-based resin composite material prepared in the embodiment of the present application before and after treatment at 2000°C;
[0034] Figure 3 This is a physical picture of the A1-high temperature resistant ceramic-based resin composite material prepared in the example of the present application before and after treatment at 2000°C. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0036] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0037] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0038] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0039] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0040] It should be noted that all raw materials and reagents in the examples of the present application were purchased on the market or prepared according to conventional methods well known to those skilled in the art.
[0041] In a first aspect, an embodiment of the present application provides a high temperature resistant ceramic-based resin composite material, the composite material comprising a fiber material matrix and a modified phenolic resin and a ceramic reinforcing slurry composited on the fiber material matrix;
[0042] The fiber material matrix includes one of carbon fiber cloth, quartz cloth or silicon carbide fiber cloth;
[0043] The modified phenolic resin is POSS modified phenolic resin;
[0044] The raw materials for preparing the ceramic reinforcement slurry include, by mass: 5-10 parts of silicon carbide powder, 15-45 parts of tantalum nitride powder, 1-10 parts of nickel powder, 10-25 parts of asphalt, and 35-50 parts of modified phenolic resin.
[0045] Among them, on the one hand, it can give the resin composite material excellent high temperature resistance. After ultra-high temperature treatment at 2000℃ (10min), the material microstructure is dense and the overall structure is complete, which can meet the continuous use in ultra-high temperature environment; on the other hand, it can give the resin composite material excellent mechanical properties, and it expands less in a continuous ultra-high temperature environment, and can maintain excellent mechanical properties after ultra-high temperature treatment; finally, it can be maintained for a long time in an ultra-high temperature environment with a high quality retention rate, meeting the application requirements of composite materials under high temperature.
[0046] It should be noted that the modified phenolic resin used in the present application is a POSS modified phenolic resin. Among them, +8 valence metal oxide and POSS are used to modify ordinary phenolic resin, and the +8 valence metal oxide is preferably osmium tetroxide, which can react chemically with the thermosetting phenolic resin methylol generated by condensation reaction under the acidic aqueous solution state of phenol and formaldehyde mixture, so that +8 valence metal osmium and POSS structure exist in the resin structure, thereby giving the composite material excellent bonding property, providing a basis for the subsequent composite of ceramic reinforcement slurry.
[0047] It should be noted that the phenolic resin used in this application is an ideal flame retardant binder due to its excellent bonding performance, outstanding ablation resistance, excellent flame retardancy, good stability, heat resistance and good mechanical properties. The phenolic resin modified by POSS has significantly improved performance in various aspects compared with the original one, especially the mechanical properties, and gives the ceramic-based resin composite material excellent high temperature resistance.
[0048] In the embodiment of the present application, the raw materials for preparing the ceramic reinforcement slurry used in the present application include, by mass: silicon carbide powder is preferably 5-10 parts, more preferably 6-8 parts, tantalum nitride powder is preferably 15-45 parts, more preferably 25-35 parts, nickel powder is preferably 1-10 parts, more preferably 4-8 parts, asphalt is preferably 10-25 parts, more preferably 15-20 parts, and modified phenolic resin is preferably 35-50 parts, more preferably 40-45 parts. Among them, by selecting and controlling the content of silicon carbide powder, tantalum nitride powder, nickel powder, asphalt and modified phenolic resin, an inorganic filler rich in chemical groups is formed, so that its structure contains active hydroxyl or carboxyl groups, which is conducive to reaction and rearrangement with phenolic resin at high temperature, and is combined into ultra-high temperature ceramics through carbon bonds. After ultra-high temperature treatment at 2000°C, the composite material is more dense.
[0049] It should be noted that the ceramic reinforcing slurry used in the present application can be pretreated by adding sodium hydroxide, a coupling agent and an organic solvent containing carboxyl and hydroxyl groups so that its structure contains active hydroxyl groups or carboxyl groups, which is beneficial to the reaction and rearrangement with the phenolic resin at high temperature, and the ultra-high temperature ceramic structure is formed through carbon bonds.
[0050] In the embodiment of the present application, the size diameter of the silicon carbide powder is preferably 200-400nm, more preferably 300-350nm; the size diameter of the tantalum nitride powder is preferably 200-400nm, more preferably 300-350nm; the size diameter of the nickel powder is preferably 10-40μm, more preferably 10-20μm. Among them, by controlling the powder size particle size of silicon carbide powder, tantalum nitride powder and nickel powder, the performance stability of the ceramic reinforcement slurry can be controlled, the slurry can be evenly dispersed on the material matrix, and a dense ceramic structure can be formed during the calcination process, thereby improving the mechanical strength, high temperature resistance and chemical stability of the material.
[0051] In the present application embodiment, the modified phenolic resin is preferably added in an amount of 0.3-0.7 times that of the composite material, and more preferably 0.42 times. Among them, the amount of modified phenolic resin added has a great influence on the performance of the composite material. Too little amount will cause uneven dispersion of the slurry, and the adhesion between the silicon carbide fiber cloth will also deteriorate, resulting in the composite material being unable to be hot-pressed. Too much addition will cause the composite material to have too much residual carbon in the high temperature process, resulting in serious expansion and deformation of the composite material as a whole, and a significant decrease in mechanical properties.
[0052] In a second aspect, the present application also provides a method for preparing the high temperature resistant ceramic-based resin composite material according to the first aspect, the method comprising:
[0053] The fiber material matrix is immersed in a solution of a modified phenolic resin and then dried to obtain a primary modified material;
[0054] Applying the ceramic reinforcing slurry on the surface of the primary modified material to obtain a secondary modified material;
[0055] calcining the secondary modified material to obtain a tertiary modified material;
[0056] Applying the ceramic reinforcing slurry on the surface of the tertiary modified material to obtain a quaternary modified material;
[0057] The four modified materials are laminated and then subjected to hot pressing to obtain the high temperature resistant ceramic-based resin composite material.
[0058] It should be noted that the preparation method provided in the present application immerses the fiber material matrix in a solution of modified phenolic resin and then dries it. After curing, it has higher mechanical properties and greatly improves high temperature resistance. The ceramic reinforcing slurry is applied to the surface of the primary modified material, and an inorganic filler rich in chemical groups is added to form a slurry that can resist high temperature ablation. Silicon carbide fiber cloth itself has the advantages of high tensile strength and tensile modulus, good heat resistance, etc. After long-term immersion in the modified phenolic resin solution, the fiber gap is filled with modified phenolic resin, and its high temperature resistance is further enhanced, and the silicon carbide fiber cloth after impregnation has better fusion with the slurry. The coated single-layer silicon carbide fiber cloth is placed in a muffle furnace and calcined at 400-600°C for 0.5-2h, which can consume most of the organic components, which can effectively reduce the expansion rate of the composite material during the next high-temperature calcination. The calcined silicon carbide fiber cloths are respectively immersed in the ceramic reinforcing slurry solution to increase the viscosity between the silicon carbide fiber cloths. The impregnated single-layer silicon carbide fiber cloth is stacked, placed in a hot pressing apparatus and hot pressed at 150-200° C. for 1.5-3 hours to prepare a high-temperature resistant ceramic-based resin composite material.
[0059] It should be noted that the fiber material matrix is a single-layer fiber cloth, and the present application preferably has 10-20 fiber cloths, and more preferably has 12-18 fiber cloths. By controlling the number of single-layer fiber cloths selected as the fiber material matrix and performing hot pressing, a composite material with uniform and stable thickness can be formed to meet the requirements in the application.
[0060] In the embodiment of the present application, the concentration of the modified phenolic resin solution is preferably 5-20%, more preferably 10-15%; the time for immersing the fiber material matrix in the modified phenolic resin solution is preferably 24-48 hours; and the drying temperature is preferably 60-80° C. Among them, by controlling the concentration of the modified phenolic resin solution and the time for immersing the fiber material matrix in the modified phenolic resin solution, the modified phenolic resin can be evenly dispersed on the fiber material, thereby improving the bonding property of the fiber matrix, and providing a basis for the subsequent composite of the ceramic reinforcement slurry.
[0061] In the embodiment of the present application, the concentration of the ceramic reinforcement slurry is preferably 10-20%, more preferably 12-17%. By controlling the concentration of the ceramic reinforcement slurry, it can be evenly bonded to the fiber surface, providing a basis for further forming a dense ceramic structure.
[0062] In the embodiment of the present application, the temperature for calcining the secondary modified material is preferably 400-600°C, and the time is preferably 0.5-2h. Among them, by controlling the temperature and time of the calcination treatment, a dense carbon layer structure can be formed on the surface of the fiber matrix, and the composite material has an obvious ceramic structure, thereby giving the composite material excellent mechanical properties. In addition, it is beneficial to remove most of the organic components in the slurry and maintain the original appearance of the silicon carbide fiber cloth, especially to partially ceramicize the slurry on the silicon carbide fiber cloth, ensuring that the residual carbon content in the phenolic resin is significantly reduced during the next high-temperature calcination and increasing the ablation resistance of the silicon carbide fiber cloth, thereby improving the high-temperature ablation resistance of the composite material.
[0063] In the embodiment of the present application, the temperature of the hot pressing treatment after laminating the four modified materials is preferably 150-200°C, more preferably 180°C, and the time is preferably 1.5-3h, more preferably 2.2h. The heating rate is 1-5°C / min. By controlling the temperature and time of hot pressing, on the one hand, a composite material of a certain thickness can be made to meet the application requirements, and on the other hand, the expansion coefficient of the material can be reduced, thereby giving the prepared resin composite material excellent mechanical properties.
[0064] It should be noted that in this application, after applying the ceramic reinforcement slurry, a calcination treatment is performed, and after applying the ceramic reinforcement slurry once, a hot pressing treatment is performed to prepare a composite material. The two coating techniques can give the resin composite material excellent high temperature resistance and mechanical properties. If only one coating is performed, the expected beneficial effect cannot be achieved; if multiple coatings are performed, not only will it cause a waste of resources, but multiple calcination treatments will also significantly reduce the mechanical properties of the material. Therefore, only by adopting the preparation process of this application can a high-temperature resistant ceramic-based resin composite material with beneficial comprehensive performance be produced.
[0065] The third aspect of the present application provides the application of the high temperature resistant ceramic-based resin composite material prepared by the preparation method described in the second aspect in a turbine rotor. The high temperature resistant ceramic-based resin composite material prepared above has excellent ultra-high temperature resistance, and after ultra-high temperature treatment at 2000°C, has excellent mechanical properties and quality retention rate, giving the manufactured turbine rotor excellent product competitiveness and having broad application prospects.
[0066] The technical solution of the present application will be further described below in conjunction with specific embodiments.
[0067] Example 1
[0068] This embodiment provides a method for preparing an Al-high temperature resistant ceramic-based resin composite material, which specifically includes:
[0069] S101: 15 single-layer silicon carbide fiber cloths are immersed in a 12% concentration modified phenolic resin solution for 32 hours, and then taken out and dried in an oven at 80° C. to obtain a primary modified material;
[0070] S102: 6 parts of silicon carbide powder, 30 parts of tantalum nitride powder, 5 parts of nickel powder, 18 parts of asphalt and 40 parts of modified phenolic resin are prepared into a ceramic reinforcement slurry, and the slurry is evenly applied to the 15 sheets of the secondary modified materials mentioned above by a coating machine;
[0071] S103: calcining 15 sheets of the secondary modified materials in a muffle furnace, the calcination time is 1.5 hours, the calcination temperature is 550° C., and the heating rate is 5° C. / min, to obtain a tertiary modified material;
[0072] S104: applying the ceramic reinforcement slurry uniformly on the third modified material by a coating machine to obtain the fourth modified material;
[0073] S105: stacking the prepared single-layer four-time modified material, placing it in a hot pressing apparatus and hot pressing it at 180° C. for 2.2 h at a heating rate of 5° C. / min, to obtain A1-high temperature resistant ceramic-based resin composite material.
[0074] Example 2
[0075] This embodiment provides a method for preparing A2-high temperature resistant ceramic-based resin composite material, which specifically includes:
[0076] S201: 15 single-layer silicon carbide fiber cloths are immersed in a 12% concentration modified phenolic resin solution for 32 hours, and then taken out and dried in an oven at 80° C. to obtain a primary modified material;
[0077] S202: 5 parts of silicon carbide powder, 45 parts of tantalum nitride powder, 1 part of nickel powder, 12 parts of asphalt and 50 parts of modified phenolic resin are prepared into a ceramic reinforcement slurry, and the slurry is evenly applied to the 15 sheets of the secondary modified materials mentioned above by a coating machine;
[0078] S203: calcining 15 sheets of the secondary modified material in a muffle furnace, the calcination time is 1.5 hours, the calcination temperature is 600° C., and the heating rate is 5° C. / min, to obtain a tertiary modified material;
[0079] S204: applying the ceramic reinforcement slurry uniformly on the third modified material by a coating machine to obtain the fourth modified material;
[0080] S205: stacking the single-layer four-time modified materials, placing them in a hot pressing apparatus and hot pressing them at 180° C. for 2.2 h at a heating rate of 5° C. / min, to obtain A2-high temperature resistant ceramic-based resin composite material.
[0081] Example 3
[0082] This embodiment provides a method for preparing A3-high temperature resistant ceramic-based resin composite material, which specifically includes:
[0083] S301: 18 single-layer silicon carbide fiber cloths are immersed in a 12% concentration modified phenolic resin solution for 32 hours, and then taken out and dried in an oven at 80° C. to obtain a primary modified material;
[0084] S302: 10 parts of silicon carbide powder, 15 parts of tantalum nitride powder, 1 part of nickel powder, 25 parts of asphalt and 35 parts of modified phenolic resin are prepared into a ceramic reinforcement slurry, and the slurry is evenly coated on the above 18 sheets of secondary modified materials by a coating machine;
[0085] S303: calcining 18 sheets of the secondary modified materials in a muffle furnace, the calcination time is 1.5 hours, the calcination temperature is 550° C., and the heating rate is 5° C. / min, to obtain a tertiary modified material;
[0086] S304: applying the ceramic reinforcement slurry uniformly on the third modified material by a coating machine to obtain the fourth modified material;
[0087] S305: stack the single-layer four-time modified materials, place them in a hot pressing apparatus, and hot press them at 180° C. for 2.2 h at a heating rate of 5° C. / min to obtain A3-high temperature resistant ceramic-based resin composite material.
[0088] Embodiment 1, embodiment 2 and embodiment 3 of the present application have basically similar comprehensive performances.
[0089] At the same time, in order to verify the comprehensive performance of the high temperature resistant ceramic-based resin composite material prepared in the above embodiment, the present application provides the following comparative examples for detailed description.
[0090] Comparative Example 1
[0091] This comparative example provides a method for preparing a B1-resin composite material, which specifically includes:
[0092] S401: 15 single-layer silicon carbide fiber cloths are immersed in a 12% concentration modified phenolic resin solution for 32 hours, and then taken out and dried in an oven at 80° C. to obtain a primary modified material;
[0093] S402: 6 parts of silicon carbide powder, 30 parts of tantalum nitride powder, 5 parts of nickel powder, 18 parts of asphalt and 40 parts of modified phenolic resin are prepared into a ceramic reinforcement slurry, and the slurry is evenly coated on the 15 sheets of the above-mentioned secondary modified materials by a coating machine;
[0094] S403: calcining 15 sheets of the secondary modified material in a muffle furnace, the calcination time is 1.5 hours, the calcination temperature is 550° C., and the heating rate is 5° C. / min to obtain a secondary modified material;
[0095] S404: stacking the prepared single-layer three-times modified material, placing it in a hot press apparatus and hot pressing it at 180°C for 2.2h with a heating rate of 5°C / min, to obtain a B1-resin composite material.
[0096] The difference between Comparative Example 1 of the present application and Example 1 is that only one layer of ceramic reinforcing slurry is applied. Since only one application is performed, the requirement of continuous use in an ultra-high temperature environment cannot be met.
[0097] Comparative Example 2
[0098] The component ratio, preparation operation and process parameters of the B2-resin composite material prepared in the comparative example of the present application are basically the same as those in Example 1, the difference being that after applying a layer of ceramic reinforcing slurry, calcination is performed, the slurry is applied twice, calcination is performed again, the ceramic reinforcing slurry is applied three times, and hot pressing is performed to obtain the B2-resin composite material.
[0099] The difference between Comparative Example 2 of the present application and Example 1 is that three layers of ceramic reinforcing slurry are applied, and the mechanical properties of the resin composite material are significantly reduced due to two calcination treatments.
[0100] Comparative Example 3
[0101] The component ratio, preparation operation and process parameters of the B3-resin composite material prepared in the comparative example of the present application are basically the same as those in Example 1, except that the modified phenolic resin is not applied, and the ceramic reinforcing slurry is used directly for treatment to obtain the B3-resin composite material.
[0102] Since the B3-resin composite material prepared in the present application is not coated with modified phenolic resin, the ceramic reinforcing slurry cannot be effectively bonded to the surface of the fiber material and cannot meet the requirements of continuous use in ultra-high temperature environments.
[0103] Comparative Example 4
[0104] The component ratio, preparation operation and process parameters of the B4-resin composite material prepared in the comparative example of the present application are basically the same as those in Example 1, except that only the modified phenolic resin is applied to obtain the B4-resin composite material.
[0105] The B4-resin composite material prepared in the present application does not have high temperature resistance because it is only coated with modified phenolic resin without adding ceramic reinforcing slurry, and therefore cannot be used in high temperature environments.
[0106] In order to verify the morphology and structure of the high temperature resistant ceramic-based resin composite material prepared in the embodiment of the present application, a scanning electron microscope test was performed on the high temperature resistant ceramic-based resin composite material prepared in the embodiment, and the results were as follows: Figure 1-Figure 2 As shown; among them, Figure 1The scanning electron microscope images of the first modified material and the third modified material in A1-high temperature resistant ceramic-based resin composite material; Figure 2 This is the scanning electron microscope image of A1-high temperature resistant ceramic-based resin composite material before and after treatment at 2000℃.
[0107] according to Figure 1 As known, the scanning electron microscope images of the first modified material and the third modified material in the A1-high temperature resistant ceramic-based resin composite material prepared in the present application, wherein a) is the first modified material, b) is the third modified material, and after the ceramic reinforced slurry is calcined at high temperature, the carbon layer formed is denser and more uniform.
[0108] according to Figure 2 As known, the scanning electron microscope images of the A1-high temperature resistant ceramic-based resin composite material prepared in the present application before and after treatment at 2000°C are shown. The prepared A1-high temperature resistant ceramic-based resin composite material is placed at 2000°C for test treatment, wherein a) is before treatment and b) is after treatment. The microstructure of the material before treatment is dense. After treatment at 2000°C for 10 minutes, although the phenolic resin in the resin composite material is cracked at high temperature, only a small part of the small molecules are volatilized, and the overall structure is intact, which further verifies that this ratio has good heat resistance.
[0109] In order to verify the high temperature resistance of the high temperature resistant ceramic-based resin composite material prepared in the embodiment of the present application, the high temperature resistant ceramic-based resin composite material prepared in the embodiment was subjected to DSC / TG test. After the sample prepared in Example 1 of the present application was subjected to DSC / TG test, it was found that the maximum exothermic peak was at 757.6°C; the material had the largest weight loss at around 700°C, with a weight loss of 8.68%, which was mainly due to the volatilization of small molecules produced by the high temperature cracking of phenolic resin. When the temperature is further increased, part of the filler is oxidized, which increases the weight, and the thermal weight loss is only 0.5% at 1600°C.
[0110] In order to verify the mechanical properties of the high temperature resistant ceramic-based resin composite material prepared in the embodiment of the present application, the high temperature resistant ceramic-based resin composite material prepared in the embodiment was tested for flexural strength, and the results are shown in Table 1. The mechanical property tests of this application are all carried out in accordance with relevant national standards, flexural strength: GB / T 6569-86. According to the test requirements in the document "Duan Liuyang; Preparation and ablation performance research of ceramic resin-based composite materials [D]; Northwestern Polytechnical University; 2020".
[0111] The A1-high temperature resistant ceramic-based resin composite material prepared in the present application was calcined at 1000°C, 1600°C and 2000°C for 10 minutes and then subjected to flexural strength tests and compared with the uncalcined resin composite material at room temperature. The test results are shown in Table 1:
[0112] Table 1 Flexural strength test results of high temperature resistant ceramic matrix resin composites
[0113]
[0114] It can be seen from Table 1 that as the treatment temperature increases, the flexural strength of the composite material decreases, especially when the flexural strength decreases significantly from room temperature to 1000°C. One reason is that the phenolic resin is thermally cracked during the heating process, resulting in structural damage; another reason is that some high-temperature fillers are oxidized during the heating process to form low-boiling point oxides and volatilize, resulting in reduced strength. According to the overall analysis of the mechanical properties after treatment at different temperatures, the high-temperature resistant ceramic-based resin composite material prepared in Example 1 of the present application has the best mechanical properties and meets the application requirements.
[0115] In order to verify the morphology and structure of the high temperature resistant ceramic-based resin composite material prepared in the embodiment of the present application after high temperature treatment, the high temperature resistant ceramic-based resin composite material prepared in the embodiment after high temperature treatment was photographed for comparison, and the results are as follows: Figure 3 As shown; among them, Figure 3 These are the actual pictures of A1-high temperature resistant ceramic-based resin composite material before and after treatment at 2000℃.
[0116] according to Figure 3 As known, the A1-high temperature resistant ceramic-based resin composite material was treated at 2000°C for 10 minutes. The upper sample is before calcination, and the lower sample is after calcination. It can be clearly seen that the calcined composite material has no obvious expansion, and the expansion rate is 7%. Therefore, the resin composite material prepared in this application can maintain good mechanical properties.
[0117] Therefore, the high temperature resistant ceramic-based resin composite material provided by the present application includes a fiber material matrix and a modified phenolic resin and a ceramic reinforcing slurry compounded on the fiber material matrix; the fiber material matrix includes one of carbon fiber cloth, quartz cloth or silicon carbide fiber cloth; the modified phenolic resin is a POSS modified phenolic resin; the raw materials for preparing the ceramic reinforcing slurry include, by mass: 5-10 parts of silicon carbide powder, 15-45 parts of tantalum nitride powder, 1-10 parts of nickel powder, 10-25 parts of asphalt, and 35-50 parts of modified phenolic resin. After being treated at an ultra-high temperature of 2000°C, the material has a dense microstructure and a complete overall structure, and has a small expansion and a high quality retention rate under continuous use conditions in an ultra-high temperature environment, and can maintain excellent mechanical properties after ultra-high temperature treatment, meeting the application requirements of composite materials at high temperatures.
[0118] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0119] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.
Claims
1. A high temperature resistant ceramic-based resin composite material, characterized in that: The composite material comprises a fiber material matrix and a modified phenolic resin and a ceramic reinforcing slurry compounded on the fiber material matrix; The fiber material matrix includes one of carbon fiber cloth, quartz cloth or silicon carbide fiber cloth; The modified phenolic resin is POSS modified phenolic resin; The raw materials for preparing the ceramic reinforcement slurry include, by mass: 5-10 parts of silicon carbide powder, 15-45 parts of tantalum nitride powder, 1-10 parts of nickel powder, 10-25 parts of asphalt, and 35-50 parts of modified phenolic resin.
2. The high temperature resistant ceramic-based resin composite material according to claim 1, characterized in that: The raw materials for preparing the ceramic reinforcement slurry include, by mass: 6-8 parts of silicon carbide powder, 25-35 parts of tantalum nitride powder, 4-8 parts of nickel powder, 15-20 parts of asphalt, and 40-45 parts of modified phenolic resin.
3. The high temperature resistant ceramic-based resin composite material according to claim 1, characterized in that: The diameter of the silicon carbide powder is 200-400nm; And / or, the diameter of the tantalum nitride powder is 200-400 nm; And / or, the nickel powder has a diameter of 10-40 μm.
4. The high temperature resistant ceramic-based resin composite material according to claim 1, characterized in that: The added amount of the modified phenolic resin is 0.3-0.7 times of the resin composite material.
5. A method for preparing a high temperature resistant ceramic-based resin composite material according to any one of claims 1 to 4, characterized in that: The method comprises: The fiber material matrix is immersed in a modified phenolic resin solution and then dried to obtain a primary modified material; Applying the ceramic reinforcing slurry on the surface of the primary modified material to obtain a secondary modified material; calcining the secondary modified material to obtain a tertiary modified material; Applying the ceramic reinforcing slurry on the surface of the tertiary modified material to obtain a quaternary modified material; The four modified materials are laminated and then subjected to hot pressing to obtain the high temperature resistant ceramic-based resin composite material.
6. The method for preparing a high temperature resistant ceramic-based resin composite material according to claim 5, characterized in that: The concentration of the modified phenolic resin solution is 5-20%; and / or, the fiber material matrix is immersed in the modified phenolic resin solution for 24-48 hours; And / or, the drying temperature is 60-80°C.
7. The method for preparing a high temperature resistant ceramic-based resin composite material according to claim 5, characterized in that: The concentration of the ceramic reinforcement slurry is 10-20%.
8. The method for preparing a high temperature resistant ceramic-based resin composite material according to claim 5, characterized in that: The secondary modified material is calcined at a temperature of 400-600° C. for a time of 0.5-2 h.
9. The method for preparing a high temperature resistant ceramic-based resin composite material according to claim 5, characterized in that: The temperature of hot pressing after laminating the four modified materials is 150-200° C. and the time is 1.5-3 hours.
10. Use of a high temperature resistant ceramic-based resin composite material prepared by the preparation method according to any one of claims 5 to 9 in the preparation of a turbine rotor.
Citation Information
Patent Citations
Method for preparing fiber reinforced multiphase ceramic matrix composite material
CN108395266A
High-strength ceramizable resin composite material and preparation method thereof
CN110216930A
Heat-proof and heat-insulation double-gradient functional composite material and preparation method thereof
CN114311870A
Copper-free friction material composition for brake pads
WO2012159286A1
